A research framework of electronic document management systems implementation process in government - Abdulkadhim, Haider (Asian Research Publishing Network (ARPN), 2015)
Many governments today have implemented Electronic Document Management Systems (EDMS). The employment of EDMS systems has increased the operational (e.g. document storage and retrieval, auditing, workflow facilities, searching and publishing) effectiveness of governments on daily basis. However, not many studies had been undertaken into process of implementing EDMS in the government context. Therefore, this paper fills this gap by presenting a research framework for the implementation process of EDMS. Based on a content analysis of the reviewed literature, this paper identifies thirteen (13) common factors contributing to the implementation process of EDMS. The factors are: (1) Top management support; (2) Budgetary; (3) Implementation planning; (4) Anti-corruption; (5) Implementation staff; (6) Security and privacy; (7) Data quality, (8) User requirements; (9) Cooperation; (10) Systems integration; (11) Awareness; (12) Resistance to change; and (13) Staff training. All these factors subsequently were linked to the Prosci-ADKAR model of change to outline the structure of EDMS implementation process framework. The proposed framework contributes to the theoretical understanding of the EAI implementation process, which may support government practitioners in implementing the EDMS applications in their government organizations. The paper also highlights with three important issues that need to be explored further while developing the framework: 1) the EDMS implementation process meaning in system development life cycle; 2) the importance of EDMS implementation factors; and 3) the kind approach to investigate EDMS implementation process.